Prosedur Pemberian Kredit Tanpa Agunan Pada PT Timexs Indonesia Di Surabaya - Ayu Indah Setyowati (Jurnal Riset Ekonomi dan Akuntansi, 2023)
This research aims to describe the procedures for providing credit without collateral at PT Timexs Indonesia in Surabaya. This type of research is qualitative research. The data collection techniques used were unstructured interview techniques, documentation and library observation. Data analysis techniques by collecting several data and interview results, displaying existing credit granting procedures, rotating existing systems, presenting and concluding research results. The results of this research show that the procedure for granting credit without collateral at PT Timexs Indonesia in Surabaya includes activities starting from submitting a credit application, filling out a form and filing a credit card with the requirements according to the provisions to the process of disbursing funds. The conclusion is that PT Timexs Indonesia has distributed credit in accordance with the provisions and is in accordance with the SOP that has been set.